A neonatal mouse model of central nervous system infections caused by Coxsackievirus B5. Issue 1 (December 2018) - Mao, Qunying; Hao, Xiaotian; Hu, Yalin; Du, Ruixiao; Lang, Shuhui; Bian, Lianlian; Gao, Fan; Yang, Ce; Cui, Bopei; Zhu, Fengcai; Shen, Lianzhong; Liang, Zhenglun
Abstract As one of the key members of the coxsackievirus B group, coxsackievirus B5 (CV-B5) can cause many central nervous system diseases, such as viral encephalitis, aseptic meningitis, and acute flaccid paralysis. Notably, epidemiological data indicate that outbreaks of CV-B5-associated central nervous system (CNS) diseases have been reported worldwide throughout history. In this study, which was conducted to promote CV-B5 vaccine and anti-virus drug research, a 3-day-old BALB/c mouse model was established using a CV-B5 clinical isolate (CV-B5/JS417) as the challenge strain. Mice challenged with CV-B5/JS417 exhibited a series of neural clinical symptoms and death with necrosis of neuronal cells in the cerebral cortex and the entire spinal cord, hindlimb muscles, and cardiomyocytes. The viral load of each tissue at various post-challenge time points suggested that CV-B5 replicated in the small intestine and was subsequently transmitted to various organs via viremia; the virus potentially entered the brain through the spinal axons, causing neuronal cell necrosis. In addition, this mouse model was used to evaluate the protective effect of a CV-B5 vaccine. The results indicated that both the inactivated CV-B5 vaccine and anti-CVB5 serum significantly protected mice from a lethal infection of CV-B5/JS417 by producing neutralizing antibodies. In summary, the first CV-B5 neonatal mouse model has been established and can sustain CNS infections in a manner similar to that observed in humans. This model will be a useful tool for studies on pathogenesis, vaccines, and anti-viral drug evaluations.